IDENTIFIKASI MODEL GAYA BELAJAR DUNN AND DUNN’S MATERI DIAGNOSA ORGANISASI PADA PESERTA PELATIHAN KEPEMIMPINAN PENGAWAS DI PUSLATBANG KDOD - Muhamad Harry Rahmadi (Jurnal Kewidyaiswaraan, 2021)
The importance of a knowledge of the participants' understanding of learning through their learning styles, will make it easier for a instructor to manage to learn. The research objective was to determine the tendency of learning style models possessed by the participants of the Supervisory Leadership Training from Dunn and Dunn’s learning style model concept, to basis for the delivery learning for Organizational Diagnostics lessons, at the KDOD Puslatbang, National Institute of Public Administration. This research is a descriptive study with a survey method in finding research data, with different data collection techniques, namely face-to-face and digital, because of the Covid-19 pandemic phenomenon. The results obtained are the learning tendency of Dunn and Dunn’s learning style model, namely the emotional learning stimulation dimension of 22% in Supervisory Leadership Training batch I, while Supervisory Leadership Training batch II of 35% and batch III of 40% is the environment, while the elements of the learning stimulus dimension from Supervisory Leadership Training batches I, II and III, there are differentiating findings, namely elements of temperature and auditory learning methods, in Supervisory Leadership Training batch I is to learn with normal temperatures and high auditory learning methods, while Supervisory Leadership Training batches II and III learn with cold temperatures and with high auditory way of learning. The difference in the implementation of the execution is the effect of the learning style model of the participant, so the need for coordination between instructor and organizers to recognize participants effectively.